A Comparision of Three Phase 27 Level Inverter Scheme under No Load and Multiple Load Conditions - C. Kannan; C.K. Kishore (Bulletin of Electrical Engineering and Informatics, 2014)
Multilevel inverters have been used in the industrial as well as the drive applications. Here three phase system of the 27 level inverter scheme with and without loads have been presented by combining the three single phase inverters of various and asymmetrical voltage ranges. Here capacitors, batteries may be used for multiple dc sources in order to achieve high voltage output. It is shown that by implementing the single phase model in the three phase system the harmonic content is lowered even in the loaded conditions than compared to the single phase system. The proposed method can be validated and simulation is carried out with the help of MATLAB/Simulink software.